Simultaneously coherent excitation of multi-modes THz radiation from dielectric loaded waveguide by pre-bunched electron beam. (23rd January 2017) - Li, Biaobin; Lu, Yalin; He, Zhigang; Li, Weiwei; Jia, Qika; Wang, Lin
Abstract: The cylindrical dielectric loaded waveguide (DLW) supports a discrete set of modes, which can be excited by electron beam passing through the structure, and the high-order modes can be the harmonics of the fundamental one by properly choosing the parameters of the DLW. By using a train of electron bunches, repeated at the fundamental frequency of the DLW, as the driving source, coherent and simultaneous excitation of multi-modes can be expected. With this proposed scheme, multi-color narrow-band THz radiation with high pulse power and high frequency can be obtained simultaneously.